Understanding factors influencing uptake and sustainable use of the PINCER intervention at scale: A qualitative evaluation using Normalisation Process Theory - Laing, Libby; Salema, Nde-eshimuni; Jeffries, Mark; Shamsuddin, Azwa; Sheikh, Aziz; Chuter, Antony; Waring, Justin; Avery, Anthony; Keers, Richard N. (PloS one, 2022)
Introduction Medication errors are an important cause of morbidity and mortality. The pharmacist-led IT-based intervention to reduce clinically important medication errors (PINCER) has demonstrated improvements in primary care medication safety, and whilst now the subject of national roll-out its optimal and sustainable use across health contexts has not been fully explored. As part of a qualitative evaluation we aimed to identify factors influencing successful adoption, embedding and sustainable use of PINCER across primary care settings in England, UK. Methods Semi-structured face-to-face or telephone interviews, including follow-up interviews and an online survey were conducted with professionals knowledgeable of PINCER. Interview recruitment targeted four early adopter regions; the survey was distributed nationally. Initial data analysis was inductive, followed by analysis using a coding framework. A deductive matrix approach was taken to map the framework to the Normalisation Process Theory (NPT). Themes were then identified. Results Fifty participants were interviewed, 18 participated in a follow-up interview. Eighty-one general practices and three Clinical Commissioning Groups completed the survey. Four themes were identified and interpreted within the relevant NPT construct: Awareness & Perceptions (Coherence), Receptivity to PINCER (Cognitive Participation), Engagement [Collective Action] and Reflections & Adaptations (Reflexive Monitoring). Variability was identified in how PINCER awareness was raised and how staff worked to operationalise the intervention. Facilitators for use included stakeholder investment, favourable evidence, inclusion in policy, incentives, fit with individual and organisational goals and positive experiences. Barriers included lack of understanding, capacity concerns, operational difficulties and the impact of COVID-19. System changes such as adding alerts on clinical systems were indicative of embedding and continued use. Conclusions The NPT helped understand motives behind engagement and the barriers and facilitators towards sustainable use. Optimising troubleshooting support and encouraging establishments to adopt an inclusive approach to intervention adoption and utilisation could help accelerate uptake and help establish ongoing sustainable use.